Developing and validating a scale for student feedback literacy in an EFL context - Fengmei Zhu; Kieran Balloo; Emma Medland; Anesa Hosein (Cogent Education)
Despite the importance of student feedback literacy (SFL) for students’ learning and the recent proliferations of SFL scales, most do not capture the discipline-specific nature of feedback practices, and few assess the change in SFL over time for intervention purposes, particularly in mainland China. Therefore, this study aimed to establish the validity of a sensitive to change student feedback literacy scale for English as a foreign language learners (SFLS-EFL). The theoretical framework that guided the scale development was principally Sutton’s Knowing-Being-Acting conceptualisation. Confirmatory Factor Analyses (CFA) with 801 EFL students in China established SFLS-EFL’s appropriate construct validity and sound stability. Criterion validity was established by correlating students’ scores on the SFLS-EFL with responses to a previously validated generic SFL scale. Five strategies were employed to ensure SFL sensitivity to change over time, which was then tested by evaluating the scale’s efficacy for detecting the effects of an SFL intervention using a sample of 76 EFL student participants. Following the intervention, the SFLS-EFL detected a larger mean increase in SFL between pre- and post-intervention than the generic SFL scale. Our SFLS-EFL is a valuable tool for understanding EFL students’ involvement in feedback processes and for evaluating the effect of feedback interventions.